High cholesterol absorption is associated with increased cardiovascular risk in haemodialysis patients: insights from the AURORA study - Silbernagel, Günther; Duarte, Kévin; Sadiku, Samir; Fauler, Günter; März, Winfried; Schmieder, Roland E; Jardine, Alan G; Massy, Ziad A; Girerd, Nicolas; Fellström, Bengt; Rossignol, Patrick; Scharnagl, Hubert; et al. (European journal of preventive cardiology, 2022)
Statin treatment did not reduce the risk of cardiovascular events in haemodialysis patients in the 4D and AURORA trials. Post hoc analyses in the 4D study suggested that high cholesterol absorption was associated with increased cardiovascular risk and that atorvastatin would reduce cardiovascular risk in haemodialysis patients with low cholesterol absorption but not in those with high cholesterol absorption.AURORA is a randomized, double-blind, placebo-controlled, multi-centre trial in haemodialysis patients. The participants were randomly assigned to receive either rosuvastatin, 10 mg daily, or a matching placebo. There was a follow-up for cardiovascular death with a median duration of 3.9 years. The cholestanol and lathosterol to cholesterol ratios were used to estimate cholesterol absorption and synthesis, respectively. Measurement of non-cholesterol sterols was available in 2332 participants of the 2733 patients included in the primary analysis of the AURORA study. A total of 598 participants died from cardiovascular diseases. The 3rd vs. the 1st tertile of the cholestanol-to-cholesterol ratio was significantly associated with increased risk of cardiovascular death [hazard ratio, HR (95% confidence interval, CI) = 1.36 (1.11-1.65)] in univariate (P = 0.002) and multivariate models (P = 0.034). In contrast, the 3rd vs. the 1st tertile of the lathosterol-to-cholesterol ratio was significantly associated with decreased risk of cardiovascular death [HR (95% CI) = 0.81 (0.67-0.99)] in univariate (P = 0.041) and multivariate (P = 0.019) models. There was no significant interaction between the cholestanol and lathosterol to cholesterol tertiles and treatment group in predicting cardiovascular death.The present data from the AURORA study confirm that high cholesterol absorption is associated with increased cardiovascular risk in haemodialysis patients. Assessment of the individual cholesterol absorption rate to guide initiation of statin treatment is not supported by the findings in the AURORA study.